Behavioural approaches to safety management practices among oil & gas workers - A. Ghani, Hairunnisa (2022)
The current study is concerned with the evaluation of a behavioural approaches to safety management practices within oil & gas workers stationed in one of the Floating, Storage and Offloading (FSO) operations. In particular, the study addresses the strengths and weakness of behavioural approaches to safety management practices and identifies both current and future potential individual and organisational learning. Employees from FSO industry in Peninsular Malaysia were participated in the study. Several methods were utilised to gather the data in relation to the study objectives including reviewing safety performance records and questionnaires. Findings from the questionnaire indicates a positive commitment to behavioural safety and safety management practices within the study organisation. Also, safety performance records of the organization recorded zero incident from quarter 1 until quarter 2 of the year 2022. The investigation findings are discussed in relation to existing theoretical frameworks of behavioural approaches and safety management practices for organizational work improvement.